The Common Good As A Social Debt and Patrimony of the Person - Ilboudo SJ, Justin (Lumen et Vita, 2015)
Aristotle’s statement that the individual human being is a social or a political animal can be misguiding if we understand it as meaning that relationships between the individual and the society are natural and obvious. Individual’s dream of autonomy and ruthless struggle to access to scarce resources on one hand and liberal and competitive societies where there is no room for “lame ducks” on the other hand, can make relationships between the person and the society conflicting and violent. The consequences can be marginalization from the social order or rebellion against it. How can we strive to make person-society relationships more integrative and fecund? In other words, what skills, social ethics as a field of Christian theology and Catholic tradition does provide for the social integration of the person and the awakening of his or her social responsibility? This paper would like to suggest and defend that the concept of the common good is a common ground for the person and the society mutual flourishing. The paragraph 26 of Gaudium et Spes defines the common good as “the sum of those conditions of social life which allow social groups and their individual members relatively thorough and ready access to their own fulfillment.” Interestingly also, Laudato Si’ builds up on the common good and defines it as “belonging to all and meant for all.” (Paragraph 23) In a more complex way, Thomas Aquinas elaborates the common good and locates it at the junction of distributive justice and piety as one’s love of his or her country. In the light of his thought, the common good as a dynamic interaction between the person and the society, becomes the cement of what Thomas Aquinas calls “civil communion.”